Preparation of bioplastic using polypropylene and starch as filler - Gupta, Arun Kumar; Malini, Subramaniam
The main objective of this contract research is to prepare bioplastic using polypropylene as matrix and other biobased materials as filler. Different categories of starch and other biodegradable materials will be used to prepare it.